Sustainable Approaches in Whey Cheese Production: A Review - Bintsis, Thomas; Papademas, Photis (My University, 2023)
Whey cheeses have been produced from the very early steps of cheesemaking practices as a sustainable way to utilize whey, which is the main by-product of cheesemaking. Traditional whey cheeses, manufactured with similar processes, are Ricotta, Ricotta salata or Ricottone, and Ricotta fresca in Italy; Anthotyros, Myzithra, Manouri, Xynomyzithra, and Urda in Greece; Urda in Serbia and Romania as well as in other countries such as Israel; Lor in Turkey; Anari in Cyprus; Skuta in Croatia and Serbia; Gjetost and Brunost in Norway; Mesost and Messmör in Sweden; Mysuostur in Iceland; Myseost in Denmark; Requeijão in Portugal; and Requesón in Spain and Mexico. The production of whey cheese is based on the denaturation of whey proteins by heating to 88–92 °C. The specific processing conditions and aspects of the microbiology of whey cheeses are discussed. The special characteristics of whey cheeses, which are high pH and high moisture content, make them susceptible to microbial growth. Due to the limited shelf life of these products, extended research has been carried out to extend the shelf life of whey cheese. The sustainable preservation approaches, such as modified atmosphere packaging, addition of herbs and/or plant extracts, and bio-preservation methods are reviewed. Moreover, novel whey cheeses focused on functional properties have developed during the last 10 years.
Keywords: Anthotyros; bio-preservation; functional whey cheeses; Lor; Manouri; Requeijão; Ricotta; sustainable preservation; Urda; whey cheese